PEMBELAJARAN VIDEO APLIKASI EDPUZZLE TERHADAP HASIL BELAJAR NAIL ART 3D SISWA SMK - Via Alqitia; Novia Restu Windayani; Dewi Lutfiati; Sri Usodoningtyas (Program Studi Pendidikan Tata Rias, 2024)
This research aims to develop appropriate learning video media on 3D acrylic nail art material, knowing students' responses and learning outcomes based on the application of existing learning video media. This research uses the Research and Development method with the Borg and Gall model, which is divided into 6 stages. This research was conducted at SMKN 1 Sooko with the subjects being phase F students majoring in skin and hair cosmetology with primary and secondary data sources. Data collection in this research used literature studies, field surveys, validation tests, learning outcomes tests, and questionnaires. The data analysis technique used is quantitative descriptive analysis which will be calculated using the average formula. The results of this research show that the media developed is suitable for application as evidenced by the validation test results of video suitability 4.31 in the good category, material suitability 4.27 in the good category, language suitability 4.15 in the good category. In its application, good results were obtained in the student response aspect, as evidenced by the average response value of 4.41, which is included in the good category. Student learning outcomes also show positive results where students are able to achieve 100% completion with a score range of 80-90. It can be concluded that this research has proceeded according to expectations and has achieved every research objective that was prepared. It is hoped that this research can be used as a basis for further research. Keywords: Nail Art, Response, Learning Results, Media Appropriateness.